Действие радиационной силы на гибкую сферическую частицу у свободной поверхности жидкости - Жук, А.П.; Жук, Я.А. (Прикладная механика, 2020)
В рамках принятого в данной работе приближения можно сделать заключение, что радиационная сила не является монотонной функцией частоты первичной волны. Характер действия радиационной силы на жидкую сферу зависит от многих факторов: частоты первичной волны, радиуса жидкой сферы, ее расстояния от свободной поверхности внешней жидкости, плотности жидкости сферической капли и скорости звука в ее жидкости. Существуют частоты первичной волны, при которых радиационная сила не действует на сферические капли. Досліджено дію радіаційної сили на сферичну краплю ідеальної рідини в околі вільної межі рідини при падінні перпендикулярно до поверхні рідини акустичної хвилі. В результаті рідинна сфера перебуває в полі стоячої хвилі звукового тиску з вузлом на вільній поверхні рідини. Мірою взаємодії є радіаційна сила: середня в часі величина інтеграла по поверхні сфери від тиску в зовнішній рідині, зумовленому акустичною хвилею. Застосовано підхід, який передбачає при визначенні тиску в рідині використання потенціалу поля швидкості, одержаного в результаті розв’язування лінійної задачі дифракції. Встановлено, що існують частоти первинної хвилі при яких радіаційна сила не діє на сферичні краплі, які, отже, будуть нерухомими. An action of the acoustic radiation force on a spherical drop of ideal liquid placed in turn in a liquid near its free plane surface is studied for the case of the incident plane sound wave propagating perpendicularly to the liquid boundary. As a result, the liquid sphere is appeared to be located in the standing sound wave of pressure which has its displacement node at the free surface. As a result, the fluid-filled sphere is under the action of the standing wave of the sound pressure with the knoе at the free surface of a fluid. The acoustic radiation force is the measure of interaction between the acoustic wave and drop; it could be defined as time-averaged integral of the sound pressure over the drop surface. To determine the pressure, an approach is developed that envisages the application of the velocity field potential obtained as a solution of the linear diffraction problem. It is found that the frequencies of the incident wave exist which provide zero radiation force acting on the drop which is therefore immobile in this case.